Surgical Treatment of Cor Triatriatum Sinister in a Cat Under Cardiopulmonary Bypass. Issue 8 (28th September 2015) - Borenstein, Nicolas; Gouni, Vassiliki; Behr, Luc; Trehiou‐Sechi, Emilie; Petit, Amandine; Misbach, Charlotte; Raillard, Mathieu; Retortillo, José Luis; Pouchelon, Jean‐Louis; Pierrel, Alain; Laborde, François; Chetboul, Valérie
Abstract : Objective: To report the surgical repair of cor triatriatum sinister (CTS) incorporating heart‐beating cardiopulmonary bypass (CPB) in a cat. Study Design: Clinical case report. Animal: Fourteen‐month‐old, 5.9‐kg male castrated Maine Coon cat. Materials and Methods: The cat had a 3 month history of inappetance, weight loss, and recurrent pulmonary edema. CTS with severe systolic pulmonary arterial (SPA) hypertension (124 mm Hg) was diagnosed by 2D echocardiography, color flow and continuous wave Doppler modes, and left atrial and pulmonary angiography. Surgery was performed through a left intercostal thoracotomy. CPB was initiated and the heart was kept beating. The left atrial appendage was opened and the intra‐atrial membrane was excised. Results: After 48 hours, the cat was doing well. Reduced SPA pressure (52 mm Hg) with decreased right heart enlargement was observed on ultrasound examination and the cat was discharged 6 days after surgery with oral antibiotics for 10 days, aspirin, and furosemide. Four months after surgery, the cat presented with increased activity and weight gain and was completely asymptomatic. Transthoracic echocardiography showed a marked improvement of all echo‐Doppler variables with disappearance of SPA hypertension (24 mm Hg). Four years after surgery, the cat was still doing well with no recurrence of clinical signs despite the lack of medical treatment. Conclusion: CTS in the cat may be successfully treated by surgery facilitated by use of CPB leading to early and long‐term substantial improvement in clinical status and cardiac function. CTS can safely be repaired under CPB in cats.